The Need for Environmental and Safety Consciousness for Sustainable Industrial Development in Nigeria: A Review - Okoye, Anthony (European Scientific Journal, ESJ, 2017)
Safety and environmental protection should be one of the strategic priorities for industries, multinational corporations, Non- Governmental organizations and indeed all Nigerians in their respective sectors. The extent of environmental and safety consciousness in Nigeria industries was reviewed in this paper. In Nigeria, industrialization and mechanization are increasing while occupational health problems are becoming prominent. On the same note, industrial development also brings, in its wake; problems of environmental pollution that often need abatement. Occupational Safety has been reported to be poor and still at infancy in Nigeria where most industries do not treat their wastes at all before discharging their effluents into the environment. The way forward for enhancing the safety and environmental consciousness were suggested. Awareness creation and enforcement are the two major steps to take to achieve a holistic safety and environmental compliance of industries